Transformation of Learning in the Digital Era: Towards Innovative and Effective Learning at MTs TPI (Taman Pendidikan Islam) Purbasinomba Paluta - Ahmad Taufik; Henrawansyah Harahap; Monica Mulyani Batubara; Leli Hasanah Lubis (Edumaspul: Jurnal Pendidikan, 2024)
The digital era has brought significant changes to the world of education, including at MTs TPI (Islamic Education Park) Purbasinomba Paluta. This research aims to explore the transformation of learning in the digital era and its impact on innovation and learning effectiveness in the school. This research uses qualitative methods with case studies. Data was collected through interviews, observation and document analysis. The research results show that MTs TPI (Islamic Education Park) Purbasinomba Paluta has implemented several forms of technology in learning, such as computers, projectors, digital learning platforms and digital teaching materials. Despite efforts to implement technology, several challenges are still faced, such as limited infrastructure, teacher competency, and student participation. To overcome this challenge, this research recommends several strategies, such as teacher training, infrastructure development, and implementation of project-based learning. This research found that the technology-based learning transformation at MTs TPI (Islamic Education Park) Purbasinomba Paluta had a positive impact on student interest and motivation, digital literacy skills, and learning outcomes. In conclusion, learning transformation in the digital era can increase innovation and learning effectiveness with the right strategy. This research provides valuable insights for other schools looking to adopt technology in their learning processes